EFEKTIVITAS PELAYANAN HUMAS SEKRETARIAT DEWAN KABUPATEN SUMEDANG - Dhesti Widya Nurhasanah Ningrum; Karen Zein Sudrajat; Lisna Mutiara Putri; Mohammad Agit Arobi (LPPM UNSAP & FISIP UNSAP, 2023)
Public relations is a form of optimizing work whose job is to create, build, improve, maintain the image and publish all forms of agency work programs. Public Relations aims to establish good cooperation with all the public so that they get direct reciprocity from the community as a form of participation and convince the public to believe in the advantages possessed by each agency. This study aims to determine the effectiveness of public relations services at the Sumedang District Council Secretariat. This study uses a qualitative method. Data collection techniques used library research, field studies (observations, interviews, and documentation), and triangulation. Informants were determined by purposive sampling technique so that this study consisted of 4 people. Meanwhile, data processing procedures use data reduction, data presentation, and conclusion drawing. The results of this study conclude that the effectiveness of public relations services at the Secretariat of the Sumedang Regency Council has been carried out well although there are still a number of things that need to be improved such as increasing the number of employees who have the ability and knowledge about public relations and protocol, and equipping facilities and infrastructure to support more public relations services. good again. But there are a number of things that support such as public relations services that are ready to serve, especially leaders 24 hours a day and serve wholeheartedly whatever the conditions are, making public relations services good. There are several suggestions, namely the importance of having supporting facilities and infrastructure for public relations in carrying out services, especially services in providing information to the community